Historical time to disease progression and progression‐free survival in patients with recurrent/refractory neuroblastoma treated in the modern era on Children's Oncology Group early‐phase trials. Issue 24 (8th September 2017) - London, Wendy B.; Bagatell, Rochelle; Weigel, Brenda J.; Fox, Elizabeth; Guo, Dongjing; Van Ryn, Collin; Naranjo, Arlene; Park, Julie R.
Abstract : BACKGROUND: Early‐phase trials in patients with recurrent neuroblastoma historically used an objective "response" of measureable disease (Response Evaluation Criteria In Solid Tumors [RECIST], without bone/bone marrow assessment) to select agents for further study. Historical cohorts may be small and potentially biased; to the authors' knowledge, disease recurrence studies from international registries are outdated. Using a large recent cohort of patients with recurrent/refractory neuroblastoma from Children's Oncology Group (COG) modern‐era early‐phase trials, the authors determined outcome and quantified parameters for designing future studies. METHODS: The first early‐phase COG trial enrollment (sequential) of 383 distinct patients with recurrent/refractory neuroblastoma on 23 phase 1, 3 phase 1/2, and 9 phase 2 trials (August 2002 to January 2014) was analyzed for progression‐free survival (PFS), overall survival (OS), and time to disease progression (TTP). Planned frontline therapy for patients with high‐risk neuroblastoma included hematopoietic stem cell transplantation (approximately two‐thirds of patients underwent ≥1 hematopoietic stem cell transplantation); 13.2% of patients received dinutuximab. RESULTS: From the time of the patient's first early‐phase trial enrollment (383 patients), the 1‐year and 4‐year PFS rates ( ± standard error) were 21% ± 2% and 6% ± 1%, respectively, whereas the 1‐year and 4‐year OS rates were 57% ± 3% and 20% ± 2%, respectively. The median TTP was 58 days (interquartile range, 31‐183 days [350 patients]); the median follow‐up was 25.3 months (33 patients were found to be without disease recurrence/progression). The median time from diagnosis to first disease recurrence/progression was 18.7 months (range, 1.4‐64.8 months) (176 patients). MYCN amplification and 11q loss of heterozygosity were prognostic of worse PFS and OS ( P = .003 and P <.0001, respectively, and P = .02 and P = .03, respectively) after early‐phase trial enrollment. CONCLUSIONS: This recent COG cohort of patients with recurrent/refractory neuroblastoma is inclusive and representative. To the authors' knowledge, the current study is the first meta‐analysis of PFS, TTP, and OS within the context of modern therapy. These results will inform the design of future phase 2 studies by providing a) historical context during the search for more effective agents; and, b) factors prognostic of PFS and OS after disease recurrence to stratify randomization. Cancer 2017;123:4914‐23 . © 2017 American Cancer Society . Abstract : To identify promising novel agents for the treatment of patients with recurrent neuroblastoma, appropriate phase 2 trial designs should be informed by historical benchmarks for progression‐free survival, time to disease progression, and overall survival, and stratified by factors prognostic of outcome after disease recurrence. The outcome for patients with recurrent neuroblastoma remains dismal. The results of this large, inclusive, representative meta‐analysis of 383 patients with recurrent neuroblastoma from 35 phase 1 trials and 2 Children's Oncology Group trials of modern‐era therapy (2002‐2014) provide context for designing new studies.